Customer orientation and firm's business performance: A moderated mediation model of environmental customer innovation and contextual factors. Issue 12 (14th November 2016) - Pekovic, Sanja; Rolland, Sylvie
Abstract : Purpose: The purpose of this study is to develop a better theoretical and empirical understanding of the causal and contextual mechanisms explaining the relationship between customer orientation and business performance. Design/methodology/approach: A three-stage least squares model was used on a sample of 3, 720 French firms with 20 or more employees. Findings: By using a moderated mediation approach, it was found that the mediating effect of environmental customer innovation on the relationship between customer orientation and business performance under different contextual factors (market environment, firm size and sector of activity) can be significantly stronger or weaker. Research limitations/implications: This analysis is restricted by the choice of one particular country, and further research should use data from other countries to develop a general understanding of the issues examined. Additionally, examining relevant mechanisms other than firm performance measures will advance the understanding of the customer orientation–firm performance linkage. Because of the fact that the majority of variables used are binary and that each survey was conducted in a particular situation and in a particular context, the picture portrayed could be biased. Because environmental issues not only concern consumers but also all other market actors, it would be highly useful to verify the obtained results using broader concepts such as Hult's (2011) "market orientation plus" concept or the "sustainable market orientation" developed by Mitchell et al. (2010). Practical implications: According to the results, to achieve market success and sustain a competitive advantage, managers must simultaneously invest in customer orientation and innovation performance. Additionally, managers should consider market environment, firm size and sector of activity as important contingencies in their decision of whether to invest in customer orientation. Originality/value: This study makes an important contribution by opening up a "black box" and offers a deeper perspective on how and why customer orientation affects firm performance. In particular, rather than providing separate analyses of mediating and moderating effects, this study proposes a simultaneous analysis that reveals how and under what conditions customer orientation improves business performance.